Titles and Semantic Violations Affect Eye Movements When Viewing Contemporary Paintings - Ganczarek, Joanna; Pietras, Karolina; Stolińska, Anna; Szubielska, Magdalena (Frontiers in Human Neuroscience, 2022)
The role of titles in perception of visual art is a topic of interesting discussions that brings together artists, curators, and researchers. Titles provide contextual cues and guide perception. They can be particularly useful when paintings include semantic violations that make them challenging for viewers, especially viewers lacking expert knowledge. The aim of this study is to investigate the effects of titles and semantic violations on eye movements. A total of 127 participants without expertise in visual art viewed 40 paintings with and without semantic violations (20 each) in one of three conditions: untitled, consistent titles and inconsistent titles. After each painting was viewed participants also rated liking and understanding. Our results suggest that titles affect the way paintings are viewed: both titled conditions were associated with shorter first fixation duration, longer saccade durations, and amplitudes and higher dynamic entropy than the untitled conditions. Titles were fixated on more frequently (but only in the time window between 1,200 and 2,800 ms) when presented alongside paintings with semantic violations than paintings without violations, and the percentage of fixations to titles was particularly high in the case of paintings with double inconsistencies (inconsistent titles and semantic violations). Also, we found that semantic violations attracted attention early on (300–900 ms), whereas titles received attention later (average first fixation on title was at 936.28 ms) and inconsistencies in titles were processed even later (after 4,000 ms). Finally, semantic violations were associated with higher dynamic entropy than paintings without violations. Our results demonstrate the importance of titles for processing of artworks, especially artworks that present a challenge for the viewers.